The Role of International Organizations and the Indonesian Government in Eradicating the Transnational Crime of Modern Child Slavery - Rininta Gustiani; Zaid; Yeni Widowaty (Universitas Pendidikan Ganesha, 2023)
Every year, a billion dollars is made in profit from human trafficking, carried out at the expense of thousands of innocent victims who are exploited by traffickers. International organizations and national governments must collaborate to solve this problem. This normative study aims to explore the role of international organizations and the Indonesian government in the fight against child trafficking, with the goal of eradicating the practice. After analyzing through prescriptive analysis, the results conclude that the International Organization has done everything possible to abolish child trafficking, including establishing comprehensive legislation through the UN Palermo Protocol and enacting Resolution 70/1, according to the research findings. This is true not only at the highest levels of the UN but also at the lowest levels of the ASEAN. The Indonesian government is still not seen as optimal in preventing child trafficking. According to the findings of this study, the government should take a more proactive approach to eradicate child trafficking by educating the public, harshly punishing perpetrators, and providing protection for victims. And these results are obtained from secondary data sources that have been collected, through the library search method, and analyzed.